Evaluation of Heavy and Trace Metals in Fingernails of Young School Children and Adults in Ilorin, Kwara State, Nigeria - HK Okoro; ST Alao; GB Adebayo; KA Basheer (Journal of Applied Sciences and Environmental Management)
Fingernail samples of young school children and selected adults were collected with respect to sex and ages in Ilorin Kwara state. The aim of this study was to determine the level of heavy metals (Fe and Cu) and trace elements (Mg and K) in the fingernails of young school children and some selected adults using atomic  absorption spectrophotometer techniques for metal analysis. Soil samples were collected from the automobile workshop of the adults examined. Sample collection and preparation were carried out using standard  procedures. The result of the study showed presences of heavy metal in the fingernails of young school children and Adults in order of Fe >Cu (0.43-6.85 μg/g, Cu 0.01-0.08 μg/g) and for essential trace metals Mg > K (Mg 0.47-1.97 μg/g, K 0.25-1.32 μg/g) respectively From the result of the study, Fe show higher concentration while Cu shows the least level. Metal concentration is higher in young school children when compared with Adults, statistical analysis show that there was significant difference between the concentrations of heavy metal in fingernails of young school children when compared with Adults. For soil samples analyzed at the automobile workshop, the concentrations of heavy metals range between Fe (344.97μg/g); Zn (2.4442 μg/g); Pb (0.93667μg/g), Cr (0.535 μg/g) and Cu (0.5017μg/g) respectively.